EFFORTS TO INCREASE ACTIVITY AND RESULTS OF LEARNING THROUGH LEARNING MODEL OF COOPERATIVE NUMBERED HEAD TOGETHER (NHT) WITH THE PROVISION OF REWARD SUBJECT IPS IN CLASS IXA SMP STATE 6 NEGARA INDONESIA - Tofan Priananda Adinata; Andika Ronggo Gumuruh; Heribertus Wicaksono (International Jurnal of Education Schoolars, 2020)
This study aims to determine the activity and student learning outcomes through Cooperative Learning Model Numbered Head Together (NHT ) by Giving Reward to Citizenship Education in Class IX of SMP Negeri 6 Negara. Application of the Numbered Head Together (NHT) Cooperative Learning Model with the Reward for Citizenship Education. it can be said that there is a significant increase where the initial reflection data on average learning outcomes, seraf power and class completeness are relatively low, but after the first cycle is implemented the results are increasing, with learning outcomes reaching an average of 74.50, and seraf reaching 74, 50%, and mastery learning reaches 80.00%. While the results of observations on the learning activities of students reached an average of 34.40 with quite active categories, and students who received active categories and above only reached 73.33%. After carrying out the second cycle showed a very significant increase, where learning outcomes reached an average of 80.00, with seraf power reaching 80%. This means there is an increase of 5.5 or 5.5% from the first cycle. Mastery learning in the second cycle reached 96.67%, this means there was an increase of 16.67% from the first cycle. While learning activities were able to reach an average of 41.93 with active categories increasing by 7.73 or 15.37% from the first cycle and students who had reached active and very active categories reached 96.67%. It means an increase of 23.33% from the first cycle. From the description above, it can be concluded that the application of the Numbered Head Together (NHT) Cooperative Learning Model with Reward Granting can significantly improve student learning activities and outcomes in the Citizenship Education Class IX A of SMP stsate 6 Negara.